The unified state qualification exam STEP-1 as a marker of the success of the education of pediatric doctors in Ukraine and Bogomolets National Medical University - Nataliya V. Obernikhina; Lesya V. Yanitska; Oksana V. Vygovska (BMC Medical Education, 2024)
Abstract Background Ukraine’s higher medical education goes deeper and deeper every year in the European integration processes in the field of «Health Care» knowledge. Since 2005, the integrated license integrated exam STEP “General medical training” has been introduced in the country to diagnose the quality of training of specialists in all medical specialties. Since 2019, Ukraine, unlike other countries in Europe and the world, has been training specialists in the specialty “Pediatrics” at the stage of undergraduate training. The quality control of the training of specialists is carried out in the form of passing the Unified State Qualification Exam STEP (USQE STEP) separately for each medical specialty (Medicine and Pediatrics). Therefore, the purpose of our research is to conduct a comparative analysis of the results of the success of the first stage of the USQE STEP-1 by students of higher medical education in the specialty “Pediatrics” with the specialty “Medicine” in Ukraine and in the Bogomolets National Medical University (Bogomolets NMU). Methods Analytical references to the results of the first stage of the USQE STEP-1 for the students who have completed theoretical medical disciplines specialty “Pediatrics” and the specialty “Medicine” in Ukraine and Bogomolets NMU, which are provided by the Testing Center at the Ministry of Health of Ukraine. Тhe statistical significance of comparative indicators was proved using Fisher’s test, with a statistical error that corresponded to the specified value for ≤ 0.05. Results It is shown that in 2022, applicants of higher medical education of Ukraine with the specialty “Pediatrics” improved the overall success rate by 8.4%, and the success rate of subtests by an average of 10.5%, despite the state of war in Ukraine. The exception was the results of the licensing exam for the subtest component “Biochemistry”: compared to 2021, the pass rate decreased by 3.6% in the specialty “Medicine” and by 6.4% in the specialty “Pediatrics”. At Bogomolets NMU, the leaders of 2022 were the students of the “Pediatrics” specialty, their success rate is 2% higher than that of the “Medicine” specialty. Conclusions The analysis of the results of USQE STEP-1 by applicants of higher medical education of the specialties “Pediatrics” and “Medicine” in Ukraine showed the effectiveness of the selection of the specialty “Pediatrics” into a separate section of the training of specialists at the undergraduate level in the field of “Health Care”. Using the methods of mathematical statistics, the effectiveness of organizational methodological techniques in the organization of the educational process in the conditions of the martial law of Ukraine and Bogomolets NMU as a leader in the training of specialists in Pediatric doctors has been proved.